Raw EPIC Data Calibration - Cede, Alexander; Kang Huang, Liang; McCauley, Gavin; Herman, Jay; Blank, Karin; Kowalewski, Matthew; Marshak, Alexander (Frontiers in Remote Sensing, 2021)
EPIC (Earth Polychromatic Imaging Camera) raw level-0 (L0) data in one channel is a 12-bit 2048x2048 pixels image array plus auxiliary data such as telemetry, temperature readings, cloud, aerosol, ocean surface and vegetation properties, sulfur dioxide, etc. The EPIC L1a processor applies a series of correction steps on the L0 data to convert them into corrected count rates (level-1a or L1a data): Dark correction, Enhanced pixel detection, Read wave correction, Latency correction, Non-linearity correction, Temperature correction, Conversion to count rates, Flat fielding, and Stray light correction. L1a images should have all instrumental effects removed and only need to be multiplied by one single number for each wavelength to obtain radiances, which are the basis for all higher-level EPIC products, such as ozone and sulfur dioxide total column amounts, vegetation index, cloud, aerosol, ocean surface and vegetation properties, etc. This paper gives an overview of the mathematics and the pre-launch and on-orbit calibration behind each correction step.